Relationship of Child Individual Factors with Stunting Incidence in Children Aged 24-36 Months at Serdang Bedagai District - Ramadhani Nainggolan; Evawany Y. Aritonang; Etti Sudaryati (Britain International for Academic Research (BIAR) Publisher, 2020)
Stunting is a form of malnutrition, as a proportion of children under 5 years old whose height is below minus 2 standard deviations based on the WHO Child Growth Standards. The purpose of the study was to determine the relationship of individual child factors with the incidence of stunting of children aged 24-36 months in Serdang Bedagai District, Sumatera Utara Province, Indonesia. This type of research is a case control study. The sample of this study amounted to 120 toddler, namely 60 cases and 60 controls with cluster sampling technique. Data was collected by interview technique using a questionnaire, and stunting data is determined by anthropometric measurements. Data analysis used chi-square test with α = 5%. The result showed that breastfeeding history, birth weight and birth length were related to the incidence of stunting in children aged 24-36 months (p <0,05; OR=2.1). It is suggested that there will be cooperation from various parties in overcoming nutritional problems during pregnancy and breastfeeding periods, such as increasing attention in the first 1000 days of human life, attention to nutrition of pregnant women as prevention of low birth weight and low birth length, which in turn affects stunting, as well as attention increase breastfeeding in infants.